'Siblings as Better Together': Social Worker Decision Making in Cases Involving Sibling Sexual Behaviour. (11th April 2017) - Yates, Peter
Abstract: Sibling abuse is arguably the most prevalent form of family violence (Meyers, 2014 ), with sibling sexual abuse more common than parental sexual abuse (Krienert and Walsh, 2011 ). However, research on social worker decision making has been limited to situations concerning parental abuse, with almost no attention paid to situations where a child in the family presents a risk. This grounded-theory study analyses from interviews with twenty-one social workers in Scotland their retrospective accounts of decisions relating to sibling living and contact arrangements regarding twenty-one families in which sibling sexual behaviour has occurred. It finds that decisions are made intuitively, influenced by a practice mindset of 'siblings as better together'. This mindset comprises three underlying perspectives: children as vulnerable and intending no sexual harm to others; sibling relationships as non-abusive and of intrinsic value; and parents as well-intentioned protective. These perspectives encourage a focus on immediate safety rather than emotional harm, and could be said to extend Dingwall et al. 's (1983) 'rule of optimism'. There is a danger of the victim child becoming lost. The study opens up a new area of research, its findings of relevance for professional groups beyond social workers including specialist nurses and other allied health professionals.